2005
DOI: 10.1111/j.1742-1241.2005.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of lichen planus with low-molecular-weight heparin (enoxaparin)

Abstract: The aim of this study is to evaluate the efficiency of low-dose, low-molecular-weight heparin (enoxaparin) in the treatment of lichen planus (LP). Twenty-four patients clinically and histopathologically diagnosed as LP with intense pruritus were treated with 3 mg of enoxaparin (Clexane), subcutaneously once a week for 4-14 weeks. Complete remission was observed in 20 of 24 patients (83%) who had widespread cutaneous involvement, but no or minimal effect was observed in four of 24 patients, three of whom had ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
3
11
0
1
Order By: Relevance
“…The mean age of the patients was 36±6.6 years and their age ranged from 20 to 50 years. Among the patients, highest percentage of patients, 21(56.8%) were in between 30 to 40 years of age, followed by 10(27%) were 40 to 50 years old and 6 (16.2%) were in between the 20-30 years of age, similar to the study finding of Kanwar It was seen that 29(78.4%) had no side effect and 8(21.6%) had side effects of drugs, not similar to the study finding of Akdeniz et al, where twenty four patients were treated by low molecular weight heparin and complete remission was observed without any side effect 15 . Similar study finding was also observed by Pacheco et al when seven patients of cutaneous lichen planus were treated with low-molecular weight heparin where marked improvement was seen without any side effect 17 .…”
Section: Discussionsupporting
confidence: 79%
“…The mean age of the patients was 36±6.6 years and their age ranged from 20 to 50 years. Among the patients, highest percentage of patients, 21(56.8%) were in between 30 to 40 years of age, followed by 10(27%) were 40 to 50 years old and 6 (16.2%) were in between the 20-30 years of age, similar to the study finding of Kanwar It was seen that 29(78.4%) had no side effect and 8(21.6%) had side effects of drugs, not similar to the study finding of Akdeniz et al, where twenty four patients were treated by low molecular weight heparin and complete remission was observed without any side effect 15 . Similar study finding was also observed by Pacheco et al when seven patients of cutaneous lichen planus were treated with low-molecular weight heparin where marked improvement was seen without any side effect 17 .…”
Section: Discussionsupporting
confidence: 79%
“…Complete remission was observed in 20 of the 24 patients (83%) who had widespread cutaneous involvement [15].…”
Section: Discussionmentioning
confidence: 99%
“…Immunmodulatorische Therapieversuche mittels Calcineurinantagonisten und niedermolekularem Heparin sind erfolgversprechend [1]. Bei fulminanten Krankheitsverläufen ist eine systemische Retinoid-(Acitretin, Isotretinoin) oder Ciclosporin-Therapie zu erwägen [3,34,46,51].…”
Section: Entzündliche Dermatosenunclassified